Estimativa da recarga natural do Aquífero Rio Claro: uma abordagem da regionalização hidrológica através da vazão de permanência - Maluta, Marcella Cipolla [UNESP] (2014)
There are Several methods available to quantify ground recharge and each method has its own limitations in terms of reliability and applicability. Most of them requires more than one parameter to estimate the groudwater recharge, as for example, coefficients for the soil type, use and occupation of the area and the evaporation and infiltration. In view of the unavailability of data in some areas, the calculation of groundwater recharge by these methods would become unavailable and often impractical. The objective of this study was to estimate the recharge from a simple method with few input data, and reliable. So, the study intended to estimate the recharge of the Rio Claro aquifer, in the Rio Claro-SP city, from a simple data obtained through the classification based on similar hydrologic areas, the technique of regionalization. The groudwater recharge was estimated by Flow Permanence of 95% (Q95), applied to the area of 95.7 km2 of occurrence of Rio Claro Formation. The study used data on rainfall for the years 2002 to 2005. To check the results, the recharge was also calculated using the application of two Indians methods, which the only input parameter was the amount of rain. The average recharge estimated by Indian methods was calculated on 315.82 mm / year and 282.94 mm / yr. The method of Q95 resulted in an average recharge of 175.4 mm / year, approximately 12% of the precipitation, which in comparison to other methods and recharges, calculated in the same area by other authors, is smaller